Ecossistemas de aprendizagens em sites de redes sociais - Rodrigues, Geovanna Cristina Falcão Soares (2019)
It analyzes how social networking sites have contributed to create learning ecosystems related to research topics in the field of Cultural Studies in Education (ECE), taking as a parameter the technological and interactive innovations possibilitated by cyberspace. The empirical field for investigation of the themes were the social networking sites Facebook and YouTube. Social Network Analysis (ARS) and Content Analysis using the NetVizz and YouTube Data Tools applications and the NodeXL Pro, Gephi and Iramuteq softwares were used as data analysis techniques. The results found point to the production of the content itself in YouTube videos and posts from Facebook shares. It was verified that users prefer to express themselves by means of icons (emoticons), being the negative reactions (dislikes, sadness or angry) minimals if compared to the positive reactions (likes and loved it) which indicates that users usually evaluate positively the materials posted and learn through them. About the content of the comments, it was noticed that the dialogues circulated around six central ideas, namely: appreciation, recognition of information resources, representation of identities, representation of social roles, expression of opinion; expression of identity and use of scientific knowledge. Considering the analysis of the results, it is argued that social networking sites by offering to users different possibilities for interaction, dialogue and content production create learning ecosystems related to ECE themes, which are being expanded as other people participate and connect to the network.